Towards activity theory - preliminary report: Ambient intelligence applied to smart education - Gonçalves, F.; Fermé, E.; Martins, A. L.; Ferreira, J. C. (Intelligent Systems Design and Applications. Advances in Intelligent Systems and Computing, 2016)
The limitations and work processes for how people work and interact are suffering changes due to the very fast development of technologies. The use of computers as daily instruments has a reflective effect on people’s activity and attitudes towards work. It is a challenge to take advantage of emergent technologies and also to overcome these technologies such as pervasive and smart places. We have changed the way we work shifting often our physical boundaries and how we operate. In this position paper we describe a simple activity analysis of a teacher’s class from a high school, based on activity theory, observations and semi-structured interviews. Specifically, we outline our perspective of ambient intelligence in smart education.